PENGARUH TATA KELOLA PERUSAHAAN DAN KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN - Yulius Kurnia Susanto; Daves Joshua (EKUITAS (Jurnal Ekonomi dan Keuangan), 2018)
The purpose of this study was to get empirical evidence about the effect of corporate governance and firm characteristic on corporate social responsibility disclosure. The corporate governance include board size, board independent, audit committee, ownership concentration, foreign ownership and public ownership. The firm characteristic include firm size, leverage, firm age, type of industry and profitability. Sample of this study consisted of 690 data from 179 non finance companies listed in Indonesia Stock Exchange from 2011 to 2014 and selected by purposive sampling method. Data were analyzed by multiple regression analysis. The results showed thatboard independent, audit committee, ownership concentration, public ownership, firm size and type of industry have an effect on corporate social responsibility disclosure. While the board size, foreign ownership, leverage, firm age and profitability have no effect on corporate social responsibility disclosure.The better the corporate governance, the control and supervision of management to disclose information about corporate social responsibility is increasing. The bigger the company, the greater the demand for the company to disclose information about corporate social responsibility.